The role of project management office in the multi-project environment. (1st January 2012) - Spalek, Seweryn
The number of projects run by companies has increased significantly over the last two decades. Therefore, apart from the challenges associated with single-project realisation, the multi-project environment created new issues that companies have needed to address. In the mid-90s of the last century, the concept of project management office (PMO) was proposed to support companies simultaneously managing numerous projects. This article discusses the role of PMO as a facilitator of the activities supporting operations in the multi-project environment. The results of the study of PMO cases are presented according to the needs addressed to them by companies.